A Legal Perspective on the Antecedents of Consumer Protection in Digital Financial Services - Novea Elysa Wardhani (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This research delves into the factors influencing consumer protection within the context of digital financial services, with a focus on the regulatory landscape, technology integration, consumer awareness, and data privacy. The primary objective is to analyze the impact of these factors on the improvement of consumer rights and safety. A quantitative approach was employed, utilizing data collected through surveys of digital financial service users. Confirmatory factor analysis was used to validate the measurement model, followed by structural equation modelling to test the hypotheses. The results demonstrate the significant and positive impact of the regulatory landscape, technology integration, consumer awareness, and data privacy on consumer protection. This study theoretically contributes by empirically confirming the role of these factors in consumer protection in digital financial services. From a practical standpoint, it underscores the importance of robust regulations, seamless technology integration, and effective consumer awareness initiatives in upholding consumer rights and safety. However, it is important to acknowledge certain limitations within this study. Its context-specific nature may restrict its generalizability to other regions, and the analysis primarily focuses on antecedent factors while neglecting potential influences from other variables. Nevertheless, this study's novelty lies in its comprehensive exploration of the foundational factors and their profound impact on consumer protection in the digital financial services landscape, furnishing valuable insights for informed policymaking and industry practices.